2015
DOI: 10.1177/1087054715584054
|View full text |Cite
|
Sign up to set email alerts
|

Managing Anxiety in Children With ADHD Using Cognitive-Behavioral Therapy: A Pilot Randomized Controlled Trial

Abstract: Non-pharmacological interventions may improve important domains of functioning for children with ADHD and anxiety, including ADHD symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
0
20
0
5
Order By: Relevance
“…Little research explicitly addresses effects of CBT on externalizing difficulties. Studies examining children with comorbid anxiety and externalizing disorders have found that CBT improves externalizing symptomology (Flannery‐Schroeder et al, 2004; Jarrett & Ollendick, 2012; Sciberras et al, 2018). Although externalizing difficulties were not primary outcomes of studies examined in this review, the present findings are in line with the extant literature.…”
Section: Discussionmentioning
confidence: 99%
“…Little research explicitly addresses effects of CBT on externalizing difficulties. Studies examining children with comorbid anxiety and externalizing disorders have found that CBT improves externalizing symptomology (Flannery‐Schroeder et al, 2004; Jarrett & Ollendick, 2012; Sciberras et al, 2018). Although externalizing difficulties were not primary outcomes of studies examined in this review, the present findings are in line with the extant literature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hiscock et al (2015) demonstrated a behavioral intervention could improve sleep in children with ADHD and that the intervention also reduced ADHD symptom severity and behavioral difficulties. Similarly, a pilot study showed promising results in the treatment of comorbid anxiety with cognitive behavioral therapy in children with ADHD, with potential flow on effects to ADHD symptoms and broader functioning (Sciberras et al, 2015). The self-reported data in this study show that these adolescents recognize that their inability to control their irritability is severely impacting their life.…”
Section: Discussionmentioning
confidence: 99%
“…Children with ADHD often experience comorbid anxiety disorders, which contributes to poorer functioning [3]. Effectively treating anxiety disorders in children with ADHD may improve functioning, including overall quality of life, for children with ADHD [4]. This article describes the protocol for the Calm Kids randomized controlled trial (RCT), which aims to evaluate the efficacy of treating comorbid anxiety disorders in children with ADHD using a manualized cognitive behavioral therapy (CBT) approach compared with usual care.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge only one randomized controlled trial (RCT) has examined the treatment of anxiety in children with a primary diagnosis of ADHD using CBT [4]. This small pilot study ( n = 12, aged 8–12 years) from our research team aimed to test the acceptability and feasibility of treating anxiety in children with ADHD using CBT (a program known as “Cool Kids”) compared with usual care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation